2017
DOI: 10.1002/da.22596
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana and other cannabinoids as a treatment for posttraumatic stress disorder: A literature review

Abstract: Posttraumatic stress disorder (PTSD) is common in the general population, yet there are limitations to the effectiveness, tolerability, and acceptability of available first-line interventions. We review the extant knowledge on the effects of marijuana and other cannabinoids on PTSD. Potential therapeutic effects of these agents may largely derive from actions on the endocannabinoid system and we review major animal and human findings in this area. Preclinical and clinical studies generally support the biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 103 publications
(126 reference statements)
1
36
2
Order By: Relevance
“…For example, excess, chronic cannabis use has been associated with a reversible downregulation of CB1 receptors in the brain (Ceccarini et al, 2015;Hirvonen et al, 2012), and both animal and human studies have found that excess cannabis use has been associated with impairments in fear extinction (Lin et al, 2008;Papini et al, 2017), possibly related to an impairment in the native functions of the eCB system. This is consistent with some clinical reports that excess cannabis use may be related to more negative, long-term outcomes in PTSD (Boden et al, 2013;Steenkamp et al, 2017;Wilkinson et al, 2016). As such, while cannabis use may provide benefit for some individuals with PTSD, and should be scientifically examined as a potential treatment approach for PTSD, caution should be exerted with respect to the potential adverse effects that could be associated with excess, chronic cannabis use.…”
Section: Toward An Endocannabinoid Deficiency Hypothesis Of Ptsd and supporting
confidence: 88%
“…For example, excess, chronic cannabis use has been associated with a reversible downregulation of CB1 receptors in the brain (Ceccarini et al, 2015;Hirvonen et al, 2012), and both animal and human studies have found that excess cannabis use has been associated with impairments in fear extinction (Lin et al, 2008;Papini et al, 2017), possibly related to an impairment in the native functions of the eCB system. This is consistent with some clinical reports that excess cannabis use may be related to more negative, long-term outcomes in PTSD (Boden et al, 2013;Steenkamp et al, 2017;Wilkinson et al, 2016). As such, while cannabis use may provide benefit for some individuals with PTSD, and should be scientifically examined as a potential treatment approach for PTSD, caution should be exerted with respect to the potential adverse effects that could be associated with excess, chronic cannabis use.…”
Section: Toward An Endocannabinoid Deficiency Hypothesis Of Ptsd and supporting
confidence: 88%
“…Cannabis use disorder prevalence and severity were not associated with PTSD, which is contrary to prior studies conducted in different populations [44][45][46][47][48]. Vietnam veterans with higher PTSD scores reported a higher frequency of cannabis use [46], and cannabis was hypothesized to help coping with PTSD symptoms such as hyperarousal, emotional distress, and intrusive thoughts of the trauma [45,47,48].…”
Section: Discussion/conclusioncontrasting
confidence: 54%
“…Vietnam veterans with higher PTSD scores reported a higher frequency of cannabis use [46], and cannabis was hypothesized to help coping with PTSD symptoms such as hyperarousal, emotional distress, and intrusive thoughts of the trauma [45,47,48]. Although prevalence for at-risk gambling was higher in our sample than in the general population (0.3-0.4%) [49], no association was found with PTSD.…”
Section: Discussion/conclusioncontrasting
confidence: 47%
“…One small randomized placebo-controlled crossover trial indicated that nabilone, a synthetic analog of Δ 9 -THC, reduced PTSD symptoms in male military personnel compared to placebo [77]. Despite the lack of randomized trials investigating cannabis use for this indication, some states allow the use of medical marijuana to treat PTSD [78,79]. This is concerning given that individuals with PTSD have a substantially increased likelihood of being diagnosed with cannabis use disorder [80].…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%